Grandi, S., Sellar, Ch. and Jafri, J. (eds.): Geofinance between Political and Financial Geographies: A Focus on the Semi-Periphery of the Global Financial System - Nagy, Erika (Hungarian Geographical Bulletin, 2020)
-